A Decision‐Centered Method to Evaluate Natural Hazards Decision Aids by Interdisciplinary Research Teams. Issue 7 (14th January 2019) - Wong‐Parodi, Gabrielle; Small, Mitchell J.
Abstract: There is a growing number of decision aids made available to the general public by those working on hazard and disaster management. When based on high‐quality scientific studies across disciplines and designed to provide a high level of usability and trust, decision aids become more likely to improve the quality of hazard risk management and response decisions. Interdisciplinary teams have a vital role to play in this process, ensuring the scientific validity and effectiveness of a decision aid across the physical science, social science, and engineering dimensions of hazard awareness, option identification, and the decisions made by individuals and communities. Often, these aids are not evaluated before being widely distributed, which could improve their impact, due to a lack of dedicated resources and guidance on how to systematically do so. In this Perspective, we present a decision‐centered method for evaluating the impact of hazard decision aids on decisionmaker preferences and choice during the design and development phase, drawing from the social and behavioral sciences and a value of information framework to inform the content, complexity, format, and overall evaluation of the decision aid. The first step involves quantifying the added value of the information contained in the decision aid. The second involves identifying the extent to which the decision aid is usable. Our method can be applied to a variety of hazards and disasters, and will allow interdisciplinary teams to more effectively evaluate the extent to which an aid can inform and improve decision making.